2002
DOI: 10.1038/nature00991
|View full text |Cite
|
Sign up to set email alerts
|

RAD6-dependent DNA repair is linked to modification of PCNA by ubiquitin and SUMO

Abstract: The RAD6 pathway is central to post-replicative DNA repair in eukaryotic cells; however, the machinery and its regulation remain poorly understood. Two principal elements of this pathway are the ubiquitin-conjugating enzymes RAD6 and the MMS2-UBC13 heterodimer, which are recruited to chromatin by the RING-finger proteins RAD18 and RAD5, respectively. Here we show that UBC9, a small ubiquitin-related modifier (SUMO)-conjugating enzyme, is also affiliated with this pathway and that proliferating cell nuclear ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
2,557
6
47

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,003 publications
(2,672 citation statements)
references
References 52 publications
62
2,557
6
47
Order By: Relevance
“…In yeast and mammalian cells, monoubiquitination of PCNA occurs on the conserved Lys 164 residue and is required for TLS function [6][7][8] . Accordingly, the increase in monoubiquitinated PCNA observed after knockdown of USP1 by siRNA requires Lys 164, as the mutation of this residue to arginine abrogated PCNA ubiquitin conjugation (Fig.…”
Section: Uv Damage Degrades Usp1 and Increases Pcna Monoubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast and mammalian cells, monoubiquitination of PCNA occurs on the conserved Lys 164 residue and is required for TLS function [6][7][8] . Accordingly, the increase in monoubiquitinated PCNA observed after knockdown of USP1 by siRNA requires Lys 164, as the mutation of this residue to arginine abrogated PCNA ubiquitin conjugation (Fig.…”
Section: Uv Damage Degrades Usp1 and Increases Pcna Monoubiquitinationmentioning
confidence: 99%
“…Protein monoubiquitination regulates the rescue of stalled DNA replication forks -an important cellular process required for cell survival 5 . The E2 ubiquitin conjugating enzyme RAD6 and the E3 ligase RAD18 are conserved in both yeast and human and they coordinate and activate the monoubiquitination of PCNA in response to UV damage or stalled replication forks [6][7][8] . Recent studies have shown that polη, a specialized TLS polymerase, is recruited to the replication fork through a specific interaction with monoubiquitinated PCNA 7 .…”
mentioning
confidence: 99%
“…Nevertheless, the exact molecular mechanisms underlying nicotine's effect on DNA repair and DNA damage tolerance remain largely unknown and controversial. Recent evidence strongly implicates ubiquitination and sumoylation in DNA replication/repair and damage tolerance [22,50].…”
Section: Discussionmentioning
confidence: 99%
“…This replacement of replicative with TLS polymerase is designated the "polymerase switch". A seminal paper by Jentsch and co-workers identified the central role of PCNA in the polymerase switch [23]. They showed that in S. cerevisiae, when the replication fork was blocked, in this case by damage inflicted by methyl methanesulfonate, PCNA became modified by ubiquitination on lysine-164.…”
Section: Recruitment To the Replication Forkmentioning
confidence: 99%
“…Further ubiquitin molecules were added in a lysine-63 linkage by the E2 heterodimer Mms2-Ubc13 and the E3 Rad5. It was proposed that mono-ubiquitination channelled the damage through an error-prone TLS pathway, whereas poly-ubiquitination channelled into an error-free pathway of damage avoidance [23,24]. This latter pathway has been postulated to involve a copy choice type of recombination involving template switching, but it is poorly understood and will not be discussed further.…”
Section: Recruitment To the Replication Forkmentioning
confidence: 99%